Carbonaceous aerosol in an urban and a rural site in the Philippines metho development and characterization - Bautista, Angel Tugade VII (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2013)
Carbonaceous aerosol, broadly classified into organic carbon (OC) and elemental carbon (EC), are atmospheric particulates known to have significant effects to health, climate, and visibility.